Contribution to the characterization of the acquisition of the emergency vigor during seed maturation - Basso, Denise Puntel [UNESP] (2018)
The stable production of high vigorous seeds regardless of the environment is a key lever to increase crop production. Seed vigor is defined as the sum of the physiological properties that lead to homogenous and vigorous seedling establishment. It includes longevity, defined as the capacity to remain viable for long periods during dry storage and the capacity to elongate after germination. However, how these traits are acquired during seed development and how the environment impacts their acquisition remain poorly understood. Yet this information is important to determine the harvest stage corresponding to maximum vigor. Using agronomy and physiological approaches on soybean and Medicago truncatula, we confirm that longevity is progressively acquired during seed maturation. In soybean, our data suggest that the climate influenced longevity whereas in Medicago, heat applied during seed maturation had no significant impact. This work also showed that HEAT SHOCK FACTOR A2.2, a homologue of HSFA9 and hub gene involved in seed maturation does not play a role in seed longevity but acts as negative regulator of embryonic dormancy. Longevity is evaluated by the ability to germinate after storage, which represents only a part of the success of crop establishment. How seed maturation affects the loss of seedling establishment capacity during storage was evaluated in soybean using an experimental system set up to assess elongation capacity. The pattern of acquisition of elongation capacity during maturation varied between crop years and growth conditions. The time to 50% loss of elongation capacity during storage was similar to that of loss of germination. Also, it increased steadily during seed maturation after mass maturity and harvest maturity stages, highlighting the importance of the late phase of seed maturation in building seed vigor.